The effect of structural parameters of pre-chamber with turbulent jet ignition system on combustion characteristics of methanol-air pre-mixture. (15th December 2022) - Wang, Bin; Xie, Fangxi; Hong, Wei; Du, Jiakun; Chen, Hong; Su, Yan
Highlights: Summarizing the current pre-chamber geometries in the database. Find four pre-chamber system's ignition modes: jet flame ignition, jet ignition, jet wake ignition, and dual-jet ignition. Discussing the causes and performance comparisons of these four ignition modes. Analysis of sensitivity for various structural characteristics of the pre-chamber. Finding that the nozzle is the most crucial component of the pre-chamber. Abstract: Pre-chamber turbulent jet ignition technology is an effective way to optimize the methanol-air mixture combustion process. A literature survey of structures of currently used pre-chambers of turbulent jet ignition systems was conducted, and three levels of four key structural factors were extracted from them, and nine pre-chambers were redesigned using the Taguchi experimental design method. The test showed that there are four typical pre-chamber ignition modes in the methanol-air mixture, namely, jet flame ignition, jet ignition, jet wake ignition, and dual-jet ignition. Compared with a spark plug, these ignition modes can increase the peak heat release rate by 15.78%, 123.51%, 136.96%, and 235.19%, respectively. When the mixture concentration in the pre-chamber is stoichiometric, the lean-burn limit for jet ignition and jet wake ignition is similar to that for spark ignition. By contrast, jet flame ignition can significantly extend the lean-burn limit. Among all the pre-chamber structural parameters, the total cross-sectional area of ​​the nozzles influenced the pre-chamber combustion performance and lean-burn limit performance the most, and the weight of the influence was always greater than 80%. The effects of the transition angle in the pre-chamber, the throat diameter, and the number of nozzles on its performance are discussed in this paper.